2022
DOI: 10.1002/ppul.26140
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative decision‐making: A framework for decision‐making about life‐sustaining treatments in children with medical complexity

Abstract: Objective Caregivers of children with medical complexity (CMC) face decisions about life‐sustaining treatments (LST) like tracheostomy. We sought to develop a clinically relevant and realistic model for decision‐making about tracheostomy placement that might apply to other LST in CMC. Design This qualitative study, conducted between 2013 and 2015, consisted of 41 interviews with 56 caregivers of CMC who had received tracheostomies and 5 focus groups of 33 healthcare providers (HCPs) at a tertiary‐care children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[26] Other studies with pediatric populations also found similar themes to this study (e.g., functional status, past medical history, prior wishes, etc.). [27, 28] Given the emotional complexities of tracheostomy decision-making, the lack of a theoretical model may contribute to the lack of efficacy of past decision-support tools for prolonged mechanical ventilation. [18] To our knowledge, this study is one of the first to use qualitative methodologies to build a theoretical model for adult tracheostomy decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Other studies with pediatric populations also found similar themes to this study (e.g., functional status, past medical history, prior wishes, etc.). [27, 28] Given the emotional complexities of tracheostomy decision-making, the lack of a theoretical model may contribute to the lack of efficacy of past decision-support tools for prolonged mechanical ventilation. [18] To our knowledge, this study is one of the first to use qualitative methodologies to build a theoretical model for adult tracheostomy decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…In a collaborative decision-making process, all practicalities of HMV need to be considered, as well as counseling about how life may change at home and the risks involved. [8][9][10] After agreeing on the start of HMV, the admission should focus on discharge planning, which should be individualized and familycentered. A smooth and safe transition involves a multidisciplinary team.…”
Section: Transition From Hospital To Homementioning
confidence: 99%
“…Before moving forward to invasive HMV, parents need to understand the long‐term prognosis and must be willing and capable to meet the child's complex needs at home. In a collaborative decision‐making process, all practicalities of HMV need to be considered, as well as counseling about how life may change at home and the risks involved 8–10 …”
Section: Transition From Hospital To Homementioning
confidence: 99%